Perancangan Dokumen Hazard Identification, Risk Assessment, and Risk Control di Area Gudang dan Perkantoran PT. X - Maria Syrilla Tasha; Kriswanto Widiawan (Jurnal Titra, 2022)
PT. X is a manufacturing company engaged in printing flexible packaging since 2017. PT. X produces plastic packaging as finished product packaging, one example of which is making packaging for food & beverages products. PT. X does not yet have an Occupational Health and Safety Management System (SMK3). The first step in realizing SMK3 at PT. X is designing a hazard identification, risk assessment, and risk control (HIRARC) document. HIRARC documents identify risks, provide risk assessments, and determine risk controls. HIRARC document design using observation and interview methods. The results of the HIRARC document show that there are 15 potential hazards, with 2 cases in the extreme category, 4 cases in the high category, 8 cases in the moderate category, and 1 in the low category. The proposed risk controls are 25 controls consisting of technical design (9 cases), administrative (11 cases), and PPE (5 cases). The design of the HIRARC document is expected to reduce the risk of hazards in the warehouse and office area. The estimated risk rating after risk control is carried out is 3 cases in the high category, 7 cases in the moderate category, and 5 cases in the low category.